Participatory Development Communication for Family Food Security during the Covid-19 Pandemic - Enggar Dwiki Egiwirantia; Nia Ashton Destrity (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2023)
The objective of this study is to elaborate and assess participatory development communication strategies employed in women's empowerment program by an Islamic non-governmental organization, specifically Lembaga Lingkungan Hidup dan Penanggulangan Bencana (LLHPB) 'Aisyiyah (Environment and Disaster Management Institute) Probolinggo City, East Java, Indonesia in 2020 to attain family food security during the Covid-19 pandemic. The three series of activities that constitute this empowerment program include training on planting vegetables, training on vegetables and fish cultivation in buckets, and engaging the online 'Aisyiyah Market group. This study utilized a case study methodology, collecting data through documentation and interviews with six informants who were committee members and members of 'Aisyiyah who are active in the empowerment initiative. This study demonstrates that, generally, the circumstance that the committee retains complete authority during crucial decision-making phases contributes to the practice of participatory communication in empowerment program. According to this study, the three activities used monologic and dialogic communication modalities in varying methods. Because collaborative member involvement only occurs when planning the formation of the 'Aisyiyah Market group, the level of member participation in the other two activities is still at a low level and only reveals involvement at the implementation and post-implementation stages of the activity.